2016
DOI: 10.1039/c6ra12905f
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and magnetic properties of Sm doped ZnO at dilute concentrations

Abstract: The work is important for the development of semiconductor devices which may create new dimensionality to control and achieve high temperature ferromagnetism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 53 publications
8
29
0
Order By: Relevance
“…Pandiyarajan et al [26] reported a lattice expansion with Sm-doping. The observed shift in the peak positions towards higher angles, however, did not continue with an increase in the doping level of Sm, i.e., no further lattice contraction is observed within error with doping concentration of 2 and 4%, which is in excellent agreement with the previously reported studies [24,31]. This trend can be tentatively attributed to a further increase in the concentration of defects and impure atoms due to the increased substitutional doping of Sm and size mismatch between the ions present in the structure.…”
Section: Xrpd Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Pandiyarajan et al [26] reported a lattice expansion with Sm-doping. The observed shift in the peak positions towards higher angles, however, did not continue with an increase in the doping level of Sm, i.e., no further lattice contraction is observed within error with doping concentration of 2 and 4%, which is in excellent agreement with the previously reported studies [24,31]. This trend can be tentatively attributed to a further increase in the concentration of defects and impure atoms due to the increased substitutional doping of Sm and size mismatch between the ions present in the structure.…”
Section: Xrpd Analysissupporting
confidence: 92%
“…One expects to observe a lattice expansion rather than a contraction due to the substitution of bigger Sm 3+ (0.964 nm) for Zn 2+ (0.74 nm); however, this strongly depends on the presence of the lattice distortion and strain and defects induced by the slight substitution of Sm 3+ . For instance, while Arora et al [31] and Kumar et al [24] found a slight lattice contraction upon Sm doping. Pandiyarajan et al [26] reported a lattice expansion with Sm-doping.…”
Section: Xrpd Analysismentioning
confidence: 99%
“…For x = 0.02 and x = 0.03 the plots show 2 straight lines with lower temperature activation energies being equal to 0.41 and 0.25 eV which corresponds to oxygen vacancies V o and Zn 2+ or Zn i with respect to high‐temperature activation energy which lies between 1.41 and 1.16 eV. A reduction in the PL intensity which is due to the reduction in zinc interstitials (Zn i ) and oxygen vacancies (V o ) for x = 0.01 clearly explains this low value of activation energy as compared to x = 0.02 and x = 0.03. It may also be noted that dc activation energy increases above x = 0.02.…”
Section: Ac Conductivitymentioning
confidence: 89%
“…Zn ions when substitutionally doped by rare earth (RE) or transition‐metal (TM) ions makes ZnO among the promising materials in the field of spintronics . It possesses optoelectronic applications, such as UV laser diode, light‐emitting diode, and photonics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation